A detailed characterization of sandalwood-filled high-density polyethylene composites. (November 2022) - Atagür, Metehan; Kaya, Nusret; Uysalman, Tuğçe; Durmuşkahya, Cenk; Sarikanat, Mehmet; Sever, Kutlay; Seki, Yoldaş
In this study, the performance of sandalwood (SW), as an efficient potential filler material for high-density polyethylene (HDPE), was investigated in detail. Firstly, the characterization of SW was conducted by the determination of chemical composition with chemical and thermal analysis methods. The distribution of SW particles, which were used in composite fabrication, was obtained by using a dynamic light scattering analyzer. Then, the composites of SW, whose weight fractions varied from 5% to 20%, with HDPE were produced in a high-speed thermokinetic mixer. The detailed characterization of composites was made by using thermogravimetric analysis, scanning electron microscopy, X-ray diffraction analysis, differential scanning calorimetry, dynamic mechanical analysis (DMA), Fourier transform infrared, thermal conductivity measurements, and tensile and three-point bending tests. From DMA, storage modulus and loss modulus values of the HDPE matrix increased with increasing the weight fraction of SW. It is clearly seen that SW incorporation into HDPE at weight fractions of 5% and 20% exhibited the best improvement in terms of tensile and flexural strengths, respectively. It can be noted that the reinforcement effect of SW for HDPE is more prominent at high temperatures.